2021
DOI: 10.1186/s40510-021-00384-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of primary dentition malocclusion on the oral health-related quality of life in preschoolers

Abstract: Background Malocclusion is a condition frequently seen in primary dentition due to the interaction of environmental, genetic and behavioural factors. The occurrence of some types of malocclusions can have an impact on oral health-related quality of life in children. Hence, the present study aimed to verify the impact of primary dentition malocclusion on oral health-related quality of life in preschool children. Methods A population-based cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In this study, the most frequently reported discomforts in the B-ECOHIS by parents/guardians were: pain in the teeth, mouth or jaws and difficulty in ingesting food and liquids. Such findings are similar to those reported by Corrêa Faria, et al (2015) and Vasconcelos, et al (2021), the latter only did not report difficulty in ingesting liquids and food, but highlighted an impairment in the pronunciation of words [7,20]. Such alterations are more evident to parents or guardians than aesthetic impairments, since they densely interfere with function [20].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In this study, the most frequently reported discomforts in the B-ECOHIS by parents/guardians were: pain in the teeth, mouth or jaws and difficulty in ingesting food and liquids. Such findings are similar to those reported by Corrêa Faria, et al (2015) and Vasconcelos, et al (2021), the latter only did not report difficulty in ingesting liquids and food, but highlighted an impairment in the pronunciation of words [7,20]. Such alterations are more evident to parents or guardians than aesthetic impairments, since they densely interfere with function [20].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the completion of the instrument is carried out by the parents/guardians. From this, the results suffer interference from the parents' perception regarding the very definition of malocclusion with the concept of OHRQOL [3,7,9,16]. This is because the presence of pain can be a determining factor for parents or guardians to perceive problems oral cavity in children, which does not usually occur in malocclusion [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The consequences of missing teeth include prolonged retention of primary teeth, infraocclusion, ankylosis, unstable occlusion, microdontia, or conical teeth 23 , 26 . According to the International Statistical Classification of Diseases for Epidemiological Purposes, dental agenesis is recognized as the failure of the tooth germ to develop and, in addition to oligodontia, is classified as hypodontia, partial anodontia, or complete anodontia 27 .…”
Section: Clinical Discussionmentioning
confidence: 99%